INTEGRASI ETNOSAINS DALAM PROJECT-BASED LEARNING UNTUK MENINGKATKAN KREATIVITAS DAN KEARIFAN LOKAL PADA MATERI PLANTAE PADA SISWA SMA DI KABUPATEN NAGEKEO - Liberius K. Dheko; Delviana Vivi Bai (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
students to meet the demands of 21st-century learning, particularly in senior high school biology subjects. One approach to developing these skills is through the integration of ethnoscience implemented using the Project-Based Learning (PjBL) model. The purpose of this study was to integrate ethnoscience into project-based learning to enhance students’ creativity and local wisdom in senior high schools in Nagekeo Regency. The research method employed was a quasi-experimental design involving two classes as samples: an experimental class that applied ethnoscience-integrated Project-Based Learning and a control class that used a cooperative learning model, with a one-group pretest–posttest research design. The research instruments consisted of test items, and data were collected through testing techniques. The results showed that in the pretest, the highest score was 76 and the lowest score was 50. In the posttest, the highest score was 95 and the lowest score was 79. The average pretest score was 61.1, while the average posttest score was 85.3. The N-gain test results indicated an average value of 0.61, which falls into the moderate category. The findings conclude that ethnoscience-integrated Project-Based Learning (PjBL) in biology learning for tenth-grade senior high school students in Nagekeo Regency is fairly effective in improving creativity and local wisdom.